Clinicopathological and Molecular Characteristics of Macroscopically Yellowish-Colored Chromophobe Renal Cell Carcinoma Compared to Non-Yellowish-Colored Chromophobe Renal Cell Carcinoma - Fumiyoshi Kojima; Ibu Matsuzaki; Naoto Kuroda; Yurina Mikasa; Fidele Y Musangile; Ryuta Iwamoto; Yuichi Takahashi; Akiko Matsubara; Yasuo Kohjimoto; Isao Hara; Shin-ichi Murata (SAGE Publishing, 2021)
Each histological variant of renal cell tumors has a unique color. The yellowish color of clear cell renal cell carcinoma (CCRCC) is explained by the presence of intracytoplasmic lipid and glycogen accumulation. Color changes in CCRCC are correlated with clinicopathological and metabolic changes, as well as biological behavior. We analyzed and compared the clinical, histopathological, and immunohistochemical features and gene expression profiles, in lipid metabolism of yellowish-colored ChRCC (ChRCC-Y), non-yellowish-colored ChRCC (ChRCC-N), and CCRCC. Of 14 ChRCCs, we retrieved 6 ChRCC-Ys. Patients with ChRCC-Y are younger than those with ChRCC-N, and the tumor is not predominant in males. ChRCC-Ys are smaller than ChRRC-Ns. Three ChRCC-Ys exhibited individual discrete tubule formation. No ChRCC-Ns exhibited individual discrete tubule formation. Two of 6 ChRCC-Ys showed relatively diffuse adipophilin positivity. No ChRCC-Ns demonstrated diffuse positivity for adipophilin. The expression of SCD, FDFT1 , and E2F1 showed a tendency to be lower in ChRCC-Y than in ChRCC-N. The expression of PDGFB showed a tendency to be higher in ChRCC-Y than in ChRCC-N. This study demonstrated ChRCC-Y did not indicate an increase in lipid and cholesterol metabolism and that ChRCC-Y did not have the common molecular alteration of CCRCC. The absence of such metabolic acceleration in ChRCC-Y might support the biological indolent behavior. Furthermore, we revealed that macroscopic color changes might be correlated with various clinicopathological features and immunohistochemical and molecular changes from different perspectives. We believe further characterization of RCC, including tumor heterogeneity, is needed to improve the management of patients with RCC.